Freezing heat: thermally imposed constraints on the daily activity patterns of a free‐ranging grassland bird. Issue 7 (23rd July 2015) - Silva, João Paulo; Catry, Inês; Palmeirim, Jorge M.; Moreira, Francisco
Abstract : Heat stress is a risk for birds exposed to high ambient temperatures, especially for those that live in open environments with limited protection from direct sun radiation. This makes them particularly vulnerable to climate warming. We studied how ambient temperature affects the daily activity of a threatened grassland bird, the little bustard Tetrax tetrax . The activity of 20 birds tracked by GPS satellite telemetry between 2009 and 2012 was monitored throughout the yearly cycle in the Iberian Peninsula. We found that temperatures over ~25°C strongly inhibited the activity of birds during the breeding and post‐breeding seasons. High temperatures were mostly frequent during mid‐day, which often forced birds to reduce activity during this period, especially during summer. We show that the expected future rise in temperatures may result in a substantial reduction in the duration of the period of the day thermally adequate for maintaining activity. With climate change inactivity levels during breeding and post‐breeding are expected to rise 37% and 59%, respectivly, compared to present standards. This may pose serious time constraints, particularly on functions like breeding and foraging, with potential consequences for individual fitness and population dynamics. Global warming may thus affect the range of birds not just through habitat change but also by limiting their activity.